FTIR-ATR monitoring and SEC/RI/MALLS characterization of ATRP synthesized hyperbranched polyacrylates - Gonçalves, Miguel A.D. (2010)
This work reports the synthesis at 1 L scale of hyperbranched polyacrylates based upon acrylate/diacrylate monomers such as n-butyl acrylate (nBA)/1,6-hexanediol diacrylate (HDDA) and using atom transfer radical polymerization (ATRP). A FTIR-ATR immersion probe was used to monitor the polymerization reaction. The dynamics of the build-up of polymer structure was studied by off-line analysis of samples at different reaction times by size exclusion chromatography (SEC) with detection of refractive index (RI) and multi-angle laser light scattering (MALLS) signals, leading to molecular weight distribution and z-average radius of gyration. Kinetic measurements and observed parameters of the molecular architecture are compared with theoretical predictions which can be used to design new synthesis strategies to improve the homogeneity of hyperbranched polymers. Another goal of this study was elucidating the impact on polymerization of secondary reactions such as intramolecular cyclizations. For comparison purposes, FRP (conventional radical polymerization) of the same monomers is also considered.